2016
DOI: 10.1097/icl.0000000000000222
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Peripheral Refraction, Higher-Order Aberrations, and Accommodative Lag With a Radial Refractive Gradient Contact Lens in Young Myopes

Abstract: Myopia should be viewed as a progressive condition associated with the potential risk of 54 visual loss. Moreover, the prevalence of myopia is increasing in Asian urban regions 55

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 76 publications
0
43
0
Order By: Relevance
“…Because of the increasing public health risk associated with myopia, many clinical research studies are evaluating possible therapeutic devices for slowing the rate of myopia progression in children. 1, 3, 27 These studies require the longitudinal assessment of refractive error changes, which necessitates clear knowledge of instrument validity and repeatability in children. Additionally, aberrometry measurements are commonly made when there is an interest in image quality, such as in studies evaluating refractive error, contact lenses for myopia control, and corneal diseases such as keratoconus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the increasing public health risk associated with myopia, many clinical research studies are evaluating possible therapeutic devices for slowing the rate of myopia progression in children. 1, 3, 27 These studies require the longitudinal assessment of refractive error changes, which necessitates clear knowledge of instrument validity and repeatability in children. Additionally, aberrometry measurements are commonly made when there is an interest in image quality, such as in studies evaluating refractive error, contact lenses for myopia control, and corneal diseases such as keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…15 Grand Seiko autorefractors (Grand Seiko Co., Hiroshima, Japan), also manufactured under the name Shin-Nippon, are frequently used in clinical studies to objectively measure refractive error because of their well-documented repeatability; however, the Grand Seiko autorefractor does not measure higher-order aberrations. 6–12 Hartmann-Shack aberrometry has been widely used in clinical research over the last several decades.…”
mentioning
confidence: 99%
“…Other studies previously have evaluated the aberrations and the light disturbance induced by wearing CL designed for myopia control. 22,32 Center-distance design MFCL, which were previously considered favorable to myopia control by producing peripheral relative myopia, were evaluated by several authors such as Fedtke et al 33 MFCL were shown to signi cantly induce positive shifts in primary SA (4th order SA), whose absolute value increased according to the increase of pupil size and add power. Dual-focus designed lenses also produced positive SA in 3 mm pupil size, but conversely, in greater pupil sizes of 4 mm, a higher negative value of 4th order SA was found, and even more so in the 5 mm pupil size.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the Cambridge Antimyopia Study, though improvements in accommodative efficiency were observed with soft contact lenses inducing negative spherical aberration, these devices were not successful in retarding axial elongation in teenagers [120]. Other studies reporting such results generally agreed that no significant changes are observed with peripheral gradient contact lenses [11], concentric dual-focus [42,122], and defocus incorporated soft contact lens [125].…”
Section: Accommodation Functionmentioning
confidence: 99%
“…In this review article, we present an overview of the recent developments of bifocal and multifocal contact lens designs for the correction of presbyopia and myopia control, including the optical design of different platforms for bifocality and multifocality, computational simulations and performance assessment, and their connection with the visual performance, patient acceptance, and efficacy. For further information on the performance of earlier designs for presbyopia correction [1,9] and myopia control, including orthokeratology [10,11], the reader must consult the abundant existing literature including several systematic reviews and meta-analyses on the former topic [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%